High pressure generation using double-stage diamond anvil technique: problems and equations of state of rhenium. Issue 2 (3rd April 2018) - Sakai, Takeshi; Yagi, Takehiko; Irifune, Tetsuo; Kadobayashi, Hirokazu; Hirao, Naohisa; Kunimoto, Takehiro; Ohfuji, Hiroaki; Kawaguchi-Imada, Saori; Ohishi, Yasuo; Tateno, Shigehiko; Hirose, Kei
ABSTRACT: We have developed a double stage diamond anvil cell (ds-DAC) technique for reproducible pressure by precisely fabricating 2nd stage anvils using a focused ion beam system. We used 2nd stage micro-anvils made of ultra-fine (< 10 nm) nano-polycrystalline diamond with various shapes and dimensions synthesized from glassy carbon at high pressure and temperature. The X-ray diffraction patterns from the rhenium sample always showed very broad peaks due to large pressure gradients in the culet of the micro-anvils. Deconvolution of the broad 101 diffraction peak results in compression of rhenium to V / V 0  = 0.633 for the smallest d-spacing. The calculated pressure for this minimum volume varies from 430 to 630 GPa, depending on the choice of the equation of state of rhenium. We conclude that the most likely pressure achieved for the minimum volume of rhenium is in a range of 430–460 GPa based on a calibration using the platinum pressure scale to 280 GPa and the latter value of 630 GPa is unreasonably high, suggesting that the pressures in an earlier study for the equation of state of rhenium would have been significantly overestimated.